OPINI MASYARAKAT TERHADAP KEGIATAN CORPORATE SOCIAL RESPONSIBILITY PT PABRIK GULA CANDI BARU - Panca Wardhana; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose of this study was to determine public opinion towards corporate social responsibility Candi Baru sugar factory. This research used descriptive quantitative method, from a population of 367 householders, while a sample of 79 respondents. The sampling technique used proportional sampling techniques and random sampling. Collecting data used literature study, questionnaires and interviews. Analyzing data used descriptive statistics. The result study stated that, Candi Baru sugar factory has conducted two types of corporate social responsibility, namely corporate social marketing and corporate philanthropy. Public opinion towards corporate social responsibility Candi Baru sugar factory has been well overall, but there were still negative opinion of the people. It caused by multiple factors, the distribution of the assistance provided was uneven, the shape and the amount of assistance provided is considered incompatible with pollution and losses caused by the activity of production companies, as well as their distrust of the objectivity of the company in selecting the target activity.